Performance criteria for generating predictive optimal control simulations of bicycle pedaling - Gidley, A. D.; Marsh, A. P.; Umberger, B. R. (Computer Methods in Biomechanics and Biomedical Engineering, 2018)
The purpose of this study was to identify one or more performance-based criteria that may be used to generate predictive optimal control simulations of submaximal pedaling. Two-legged pedaling simulations were generated based on minimizing muscle activation, muscle stress, metabolic energy, time derivative of muscle force, and minimizing metabolic energy while pedaling smoothly. The simulations based on minimizing muscle activation and muscle stress most closely matched experimental pedaling data, with the activation criterion better matching experimental muscle activation timing. We conclude that predictive simulations of submaximal pedaling may be generated using a cost function based on minimizing muscle activation.